Carbon-copper (C-Cu) composites using local carbon material through warm compaction process for potential electrical and electronic applications - Ibrahim, M. H. I.; Abdul Razak, M. I.; Mustafa, N.; Selamat, M. A. (Asian Research Publishing Network (ARPN), 2016)
The carbon-copper (C-Cu) composites combine the positive characteristics of thermal and electrical conductivity from Cu, low thermal expansion coefficient and lubricating properties from conventional carbon/graphite. For that particular application, C-Cu composites are widely used as electrical contact devices such as carbon brushes and current collector for railway power collection system. Due to economic and environment concern, activated carbon produced from MPOB oil palm kernel shell (OPKS) is studies as replacement for conventional carbon/graphite in C-Cu composites. This study intended to investigate the effect in term of characterisation using different particle size of carbon (<90μm and <150μm) and determine the optimum parameter of C-Cu composites to enhance the physical and mechanical properties. The preparation for producing the sample was started with the OPKS through the crushing and sieving process as well as mixed with copper powder and epoxy resin at selected ratio before it is compacted into shape and then undergoes with warm compaction and post baking process. The effects of different particle size of carbon to physical and mechanical properties of the C-Cu composites were analysed. It is found that the improvements of the mechanical and physical properties are strongly affected by the fine particle carbon (<150µm) and after passing warm compaction at 150 ˚C and post baking at 200 ˚C conditions. It is concluded that the sample prepared in ratio 65% C (<150µm) + 20% Cu + 15% Epoxy resin with